"Good Australians Will Respond": Transforming the Work Ethic in Popular Media, 1941–1945. Issue 1 (2nd January 2023) - Coatney, Caryn
ABSTRACT: Media images of heroic, hard-working Australian achievers have often accompanied stories about an upbeat national work ethic to boost public morale in times of massive upheavals and crisis. The concept of an Australian work ethic has not been a natural creation, but it has been actively developed in the media. This article reveals a turning point in the media portrayal of the crucial area of work that helped cultivate diverse expressions of Australia's image. The article focuses on the era of momentous disruption in World War II that led to an unprecedented idealisation of workers and changed the traditional roles of the prime minister, journalists and the public. Wartime prime minister John Curtin became an egalitarian partner and a collaborator with media teams. Journalists created increasingly inclusive media experiences to encourage the public to identify with the fashionable new ethos of working-class thrift. Wartime citizens enthusiastically contributed to the varied media expressions of collective work ethics, overturning the traditional notion of a passive public sphere. Using the concept of the emotional public sphere, this article provides a rare perspective on the media's role in shaping and extending popular attitudes towards Australian workers, collective service and inclusive communities.